Dopamine versus dobutamine in very low birthweight infants: endocrine effects. Issue 5 (28th February 2007) - Filippi, Luca; Pezzati, Marco; Poggi, Chiara; Rossi, Sauro; Cecchi, Alessandra; Santoro, Cristina
Abstract : Objectives: To compare the endocrine effects of dopamine and dobutamine in hypotensive very low birthweight (VLBW) infants. Design: Non-blinded randomised prospective trial. Setting: Level III neonatal intensive care unit. Patients: 35 hypotensive VLBW infants who did not respond to volume loading, assigned to receive dopamine or dobutamine. Measurements: Haemodynamic variables and serum levels of thyroid stimulating hormone (TSH), total thyroxine (T4 ), prolactin (PRL) and growth hormone were assessed during the first 72 h of treatment and the first 72 h after stopping treatment. Results: Demographic and clinical data did not significantly differ between the two groups. Necessary cumulative and mean drug doses and maximum infusion required to normalise blood pressure were significantly higher in the dobutamine than in the dopamine group (p<0.01). Suppression of TSH, T4 and PRL was observed in dopamine-treated newborns from 12 h of treatment onwards, whereas levels of growth hormone reduced significantly only at 12 h and 36 h of treatment (p<0.01). TSH, T4 and PRL rebound was observed from the first day onwards after stopping dopamine. Dobutamine administration did not alter the profile of any of the hormones and no rebound was observed after stopping treatment. Conclusion: Dopamine and dobutamine both increase the systemic blood pressure, though dopamine is more effective. Dopamine reduces serum levels of TSH, T4 and PRL in VLBW infants but such suppression is quickly reversed after treatment is stopped. Further research is required to assess if short-term iatrogenic pituitary suppression has longer-term consequences.